AN ESTIMATION OF THE MAXIMUM B-VALUE IN THE GUTENBERG-RICHTER RELATION - Olsson R. (My University, 1999)
An estimation of the maximum b-value in the Gutenberg-Richter relation is achieved from empirical laws of earthquake occurrence and from dimensional considerations of power law distributions of earthquake size. The deduced maximum b-value, 1.5 (or with error limits 1.30=<bmax=<1.64) agrees very well with maximum b-values computed from earthquake catalogues or published elsewhere in the literature. (C) 1999 Elsevier Science Ltd. All rights reserved.